Seed Quality as Influenced by Accelerated and Natural Ageing in Bitter Gourd (Momordica charantia L.) - SHANTAPPA TIRAKANNANAVAR; M.N. MERWADE; M. SHEKHARGOUDA; LAXMAN KUKANOOR; S.B. BELLAD (Seed Research, 2026)
Fresh and one year old seeds of bitter gourd (Momordica charantia L.) were subjected to accelerated ageing treatment (98 + 1% RH, 42 ± 1°C) for six days. The results showed that, one day of accelerated ageing recorded significantly higher germination (90.30%), vigour index (3029), field emergence (86.20%) and lower electrical conductivity (0.340 dSm²) compared to other ageing treatments irrespective of age of the seeds. Increase in germination value noticed in one day of accelerated aged seeds over no ageing might be due to the higher germination recorded by one day of accelerated ageing of fresh seeds as compared to one year old seeds. Three days of accelerated ageing recorded 87.20 per cent germination, which is comparable (87.00%) to 12 months of natural ageing.